2021
DOI: 10.1016/j.jvs.2020.08.115
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the operative threshold for abdominal aortic aneurysm repair in the context of COVID-19

Abstract: Objective The worldwide pandemic involving the novel respiratory syndrome (COVID-19) has forced healthcare systems to delay elective operations, including abdominal aortic aneurysm (AAA) repair, to conserve resources. This study provides a structured analysis of the decision to delay AAA repair and quantify the potential for harm. Methods A decision tree was constructed modeling immediate repair of AAA relative to an initial non-operative (delayed repair) approach. Risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
(40 reference statements)
1
15
0
2
Order By: Relevance
“…Patients with large aneurysms (>7 cm) faced a 5.4% to 7.7% absolute increase in the probability of mortality with a delay of repair of 3 months, but demonstrated a higher probability of survival when treated with immediate endovascular repair or open surgery. Immediate endovascular repair had a higher probability of survival for smaller aneurysms (5.5 to 6.9 cm) except in settings with a high probability of COVID-19 infection (10%-30%) and advanced age (70-85 years) [15] .…”
Section: Discussionmentioning
confidence: 92%
“…Patients with large aneurysms (>7 cm) faced a 5.4% to 7.7% absolute increase in the probability of mortality with a delay of repair of 3 months, but demonstrated a higher probability of survival when treated with immediate endovascular repair or open surgery. Immediate endovascular repair had a higher probability of survival for smaller aneurysms (5.5 to 6.9 cm) except in settings with a high probability of COVID-19 infection (10%-30%) and advanced age (70-85 years) [15] .…”
Section: Discussionmentioning
confidence: 92%
“…After the analysis on the habits of 23 surgeons from 18 countries, all of the participants agreed to use maximum personal protection equipment for every patient without regard to the patient's COVID‐19 status [13] . McGuinness et al [29] showed that health care providers older than 50 years have ≥0.5% chance of mortality if they contract COVID-19. It is noteworthy how this mortality rate is greater than the survival benefit in a 3-month time horizon for aneurysms.…”
Section: Resultsmentioning
confidence: 99%
“…However, regional incidence of COVID-19 and health care system status may modify these recommendations. According to McGuinness et al [29] , a 60-year-old patient has a risk of death associated with COVID-19 of about 0.6%. On the contrary, the same patient with a relatively small (5.5 to 5.9 cm) aneurysm would be exposed to a higher time-related risk of death (0.8% at 3 months and 1.9% at 6 months).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent modelling study in the United States explored the trade-off between COVID-19 mortality and AAA-related mortality. The work focussed on the delay versus immediate repair decision for those with large AAAs, akin to considering an increased threshold for elective surgery [ 16 ]. The study uses a decision tree approach rather than the event simulation, rate-based approach used here.…”
Section: Discussionmentioning
confidence: 99%